PENGARUH TERAPI MUSIK TERHADAP KECEMASAN IBU HAMIL DI DESA SIGULANG KECAMATAN PADANGSIDIMPUAN TENGGARA - tanjung, wiwi wardani; Apripan, Rika (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
Pregnancy is an exciting time and is awaited by mothers and families. All mothers want their pregnancies and deliveries to go safely, smoothly, and normally. However, pregnancy is also a time of excitement and worry. Pregnancy can be a period of crisis in which the mother often feels worried or afraid of the pain and physical dangers that arise during childbirth. This causes bleeding in pregnant women during childbirth. The purpose of this study was to determine the effect of music therapy on reducing anxiety of pregnant women in Sigulang Village, Padangsidimpuan Tenggara District, health. The research used was quasi-experimental research (pseudo-experiment) using the Prettest posttest only research design. The research site is in Sigulang Village, Padangsidimpuan Tenggara District. The study population was 20 pregnant women, the study sample was 20 people. Data analysis using univariate analysis and bivariate analysis. The results showed that there was a decrease in anxiety of pregnant women and the average anxiety score of pregnant women before religious music therapy was 35.33 and after religious music therapy there was a decrease in anxiety with an average of 25.83. The p-value is 0.001, meaning that there is an effect of music therapy on reducing anxiety. The implication of this study is that the provision of religious music therapy can reduce anxiety in pregnant women when facing childbirth.